Perception of the Contribution of Collaborative Economy to the Sustainable Development Goals - Amezcua Nunez, Juan Bernardo; Ruiz Vigil, Ana Lucía; Méndez Wong, Adriana (RAN - Revista Academia & Negocios, 2024)
Purpose: To assess self-perception of sharing economy (SE) online platform users regarding their contribution to achieving Sustainable Development Goals (SDGs). Methodology: An electronic survey through convenience sampling, targeting 500 users of sharing economy online platforms. Structural equation modeling with Partial Least Squares (PLS SEM) was employed to model relationships among latent variables such as the use of circular economy applications, acceptance of these applications, and perceptions of their impact on the SDGs compliance. Results: SE users perceive that their participation contributes to achieving the SDGs by helping to protect the environment, improve social welfare, and promote economic growth. They acknowledge the importance of participation from businesses and governments to ensure SE is sustainable and has a positive societal impact. Implications: The study validates users’ perspectives and provides empirical evidence supporting the theory that SE can be an effective tool for achieving the SDGs. These findings can guide businesses, governments, and civil society organizations in implementing strategies to promote adoption of sustainable practices within SE. Originality: This research innovates by exploring how users’ perceptions of SE applications impact sustainable consumption behaviors and intersectoral collaborations. It offers new theoretical and practical insights to promote business practices and public policies aligned with the SDGs.